Preliminary Exploration of Obesity-Related Eating Behaviour Patterns in a Sample of Saudi Preschoolers Aged 2–6 Years through the Children’s Eating Behaviour Questionnaire - Ali H. Al-Hamad (MDPI AG, 2021)
Background: The Children’s Eating Behaviour Questionnaire (CEBQ) is used with parents to determine the characteristics of eating behaviour of their children and, consequently, children’s propensity to become obese. It has been successfully used mainly in Western countries, but not in Saudi Arabia. In this pilot study, we explored the use of the Saudi version of the CEBQ for preschool children aged 2–6 years in Saudi Arabia, and assessed the associations between eating behaviours and children’s age, gender and relative weight and parental weight. Methods: Parents of 200 Saudi preschool children in Riyadh completed the Saudi version of the CEBQ. Factor analyses on all CEBQ items were performed and differences between genders and age groups were examined. Correlations between children’s BMI z-scores and eating behaviours were analysed using linear regression. Results: The factor analysis revealed an eight-factor solution similar to the theoretical factor structure, with good internal reliability and acceptable correlations between subscales. Boys scored higher than girls on food responsiveness; no difference between age groups was found. Positive associations between BMI z-scores and ‘food approach’ subscales, food responsiveness, enjoyment of food and emotional overeating were found, while ‘food avoidant’ subscales, satiety responsiveness and slowness in eating had inverse relationships with BMI z-scores. Maternal BMI had a positive association with BMI z-scores and food responsiveness. Conclusion: The CEBQ is a valid psychometric tool that can be reliably used to assess eating behaviour characteristics in Saudi preschool children.